Performa Pertumbuhan dan Produksi Karkas Mandalung Hasil Hibridisasi antara Entok Jantan (Cairina moschata) dengan Itik Betina (Anas plathyrynchos) (The Growth Performance and Production of Carcass Mandalung, Hybridized from Male Muscovy Ducks (Cairina moschata) and Female Ducks (Anas plathyrynchos)) - Danang Priyambodo; Jakaria Jakaria; Rukmiasih Rukmiasih (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2015)
Crossbreeding between species (hybridization) was conducted to obtain higher average value of offspring trait than the parent trait. The aim of this study was to determine the best type of mule duck and to evaluate the heterosis effect appearing on mule duck obtained. The experimental design used was a randomized block design with two levels of treatment and eight groups based on the hatching period. The treatments were the type of mule duck crossed between muscovy duck male with female cihateup duck (EC) and mule duck crossed between male muscovy duck with female alabio duck (EA). The results showed the growth performance and carcass production of EC and EA mule duck were not significantly different, but mule duck EC tended to show better results than mule duck EA. The percentage of heterosis effect produced by EC and EA mule duck in growth performance and carcass production showed advantages over the parent. EC mule duck had a higher level of heterosis than EA mule duck for some trait observed. EC mule duck can be kept as best crossbreed to produce mule duck with good performance and carcass production.Keywords: mule duck, performance, carcass production, heterosis